Garden of Light - Continuing Whispers. - Fujii, Aki; Mori, Chika; Okamura, Keiko; Chinzei, Yoshimi (Tokyo : Museum of Contemporary Art Tokyo, 2022)
Nakanishi, Natsuyuki ; Ishikawa, Yukie ; Domoto, Yuumi ; Lee, Ufan ; Fontana, Luio ; Usami, Keiji ; Arakawa, Shusaku ; Mise, Natsunosuke ; Kou, Kana ; Suzuki, Hiraku ; Fulton, Hamish ; Hiwasaki, Takao ; Komai, Tetsuro ; Hamada, Chimei ; Funakoshi, Katsura ; Fukuda, Naoyo ; Boltanski, Christian ; Weerasethakul, Apichatpong
Garden of Light - Continuing Whispers, Museum of Contemporary Art Tokyo, Collection Gallery, 19 March - 19 June 2022
boek